Manifestasi Budaya Patriarki Yang Menimbulkan Korban Pada Novel “Cantik Itu Luka” Karya Eka Kurniawan - Adhilla, Nissa; Tutrianto, Rio (Journal of Knowledge and Collaboration, 2025)
This research reveals a patriarchal culture that places women as victims and men as the main power holders, as depicted in the novel Cantik itu Luka by Eka Kurniawan. This culture makes women sexual objects, especially in the economic context, which triggers acts of sexual violence. With a descriptive approach and a narrative criminology method, this study examines the teaching value of fictional narratives in the novel. The results of the study show the radical feminist view that women's suffering comes from male domination. This novel is a means of criticism of the patriarchal culture that oppresses women through male power.